Mitigation strategies for enteric methane emission with special emphasis on biological approaches: A review - Malik, P K; Singhal, K K; Deshpande, S B; Siddique, R A (The Indian Journal of Animal Sciences, 2012)
Atmospheric concentration methane is almost 1782 ppb, which is 155% higher than its pre industrial concentration. Agricultural sector dispensing a consequential amount of methane (about 2/3rd of total anthropogenic); livestock rearing generates 7–12 Tg methane annually from the country. The methane generation from ruminants not only contributes significantly to global warming but also leads a loss of dietary energy (7–12% of GEI). This loss needs attention, where acute shortage of quality feeds prevails. Efforts were made in the past to control the enteric methane emission using customary feeding approaches including chemicals and methane analogues, but most of them dubitable with one or more critical limitations like few respond at high doses, toxicity to either host animal or inhabited synergistic microbes etc. Therefore, the search for suitable, effective and safe methane mitigating agent is still ongoing, and extensive screenings of newer strategies are on radar of animal nutritionist and microbiologists in association with biotechnologists for abatement of methane emission from ruminants. This review paper examines the biological approaches such as reductive acetogenesis, immunization, phage therapy, defaunation, disabling the protein bindings accountable for association of methanogens with other microorganisms in rumen. In conclusion, there is the foremost need to explore the potentialities of state-of-the-art biological approaches under in vivo and with topographical variations.